UJI EFEKTIVITAS BEBERAPA ISOLAT JAMUR ANTAGONIS (Trichoderma sp.) ASAL LIMBAH MEDIA TANAM JAMUR MERANG TERHADAP INTENSITAS BEBERAPA PENYAKIT PENTING PADA TANAMAN KEDELAI (Glycine max L.) - Fitrianingtyas, Annisa Dwi Rahayu; Adhi, Satriyo Restu; Mustikasari, Fauzia (Universitas Islam Kadiri, 2025)
Disease attacks remain a significant issue in the soybean cultivation process. The purpose of this study is to determine the most effective antagonist fungus isolate (Trichoderma sp.) from mushroom-growing medium waste in suppressing the intensity of several important diseases in soybean plants (Glycine max L.). The research method to be used is a Single Factor Randomized Block Design (RBD) experiment, consisting of 8 treatments and 4 replications. The treatments are as follows: A0 (Control), A1 (Trichoderma sp. 1), A2 (Trichoderma sp. 2), A3 (Trichoderma sp. 3), A4 (Trichoderma sp. 4), A5 (Trichoderma sp. 5), A6 (Commercial Trichoderma sp.), and A7 (Synthetic Fungicide). The study results showed the presence of 4 diseases: frogeye leaf spot (Cercospora sojina), purple seed stain (Cercospora kikuchii Mats.), bacterial pustule (Xanthomonas axonopodis), and soybean mosaic virus (Soybean mosaic virus). The variance analysis and further DMRT (Duncan Multiple Range Test) at a 95% confidence level showed that treatment A3 (Trichoderma sp. 3) resulted in the lowest disease severity intensity of bacterial pustule (0.85%). Treatments A2 (Trichoderma sp. 2) and A3 (Trichoderma sp. 3) resulted in the lowest incidence intensity of bacterial pustule (15.48%). Treatments A3 (Trichoderma sp. 3) and A4 (Trichoderma sp. 4) showed the lowest incidence intensity of purple seed stain (25%). Treatment A5 (Trichoderma sp. 5) resulted in the highest wet seed weight (13.58 g) and the highest dry seed weight (5.74 g). Treatments A2, A3, and A4 can be recommended for disease control to reduce the severity and incidence intensity of diseases. Treatment A5 can be recommended for increasing the seed weight yield in soybean plants.